Should We Teach English Early? (Some Considerations) - Patuan Raja (TEFLIN Journal: A publication on the teaching and learning of English, 2001)
English has been introduced in early levels of elementary schools apparently based on the assumption the earlier the better. The present article reviews some literature on the ralation between age and second language acqusition and has to conclude that the assumption does not have solid foundation. It also discusses the implications relevant to Indonesian context, especially concerning amount of instructional time, educational value, and resources.